The acquisition of verb morphology by a group of spanish monolingual children - Vásquez, Luz Marina (Universidad de Costa Rica, 2016)
Spanish has a rich verb inflectional system with up to 53 inflectional verb forms distributed between regular and irregular verbs and in which roots are always bound, as verbs must contain markings for person, tense/aspect, and number. The acquisition of verb morphology by native speakers reportedly reflects this complexity in that children produce multiple non-target-like forms wherein tense, person, and number errors are found. This study reports all verb forms identified in the spontaneous speech by a group of 15 native Spanish-speaking children ages 3;6 to 5;6. The analysis of all 233 verb forms analyzed revealed some pronunciation errors, number agreement errors, errors in the use of clitic pronouns, and incorrect use of person and tense agreement.  The majority of non-target-like forms identified consisted of regularization of verb forms wherein regular conjugation morphemes were attached to irregular verbs. A few –ar type verbs additionally showed ir-regularization of regular verbs, as children used conjugations which apply to irregular verbs with regular verbs.